A Novel 2D Porous Print Fabric-like α-Fe2O3 Sheet with High Performance as the Anode Material for Lithium-ion Battery. (10th September 2016) - Zhang, Suyue; Zhang, Peigen; Xie, Anjian; Li, Shikuo; Huang, Fangzhi; Shen, Yuhua
Abstract: Anode materials are very crucial in lithium ion batteries. Exploring the simple and low cost production of anodes with excellent electrochemical performance remains a great challenge. Here, we used natural flower spikes of Typha orientalis as the bio-templates and organizers to prepare a novel two-dimensional (2D) porous print fabric-like α-Fe2 O3 sheet with thickness of about 30 nm. The prepared large-area sheets were orderly assembled by many nanosheets or nanoparticles, and two kinds of pore structures, such as pores with average diameter of about 50 nm or pore channels with aspect ratio of ca. 4, presented between adjacent nanosheets. The pre-treatment by ammonium for flower spikes has a great effect on the microstructure and electrochemical performance of the products. As the anode material for lithium ion battery (LIB), the as-obtained porous print fabric-like α-Fe2 O3 sheets show an initial discharge capacity of 2264 mA h g −1 and the specific capacity of 1028 mA h g −1 after 100 cycles at a current density of 500 mA g −1, which is higher than the theoretical capacity of α-Fe2 O3 (1007 mA h g −1 ). This highly reversible capacity is attributed to the very thin large-area sheet structure, and many pores or pore channels among the interconnected nanosheets, which could increase lithium-ion mobility, facilitate the transport of electrons and shorten the distance for Li + diffusion, and also buffer large volume changes of the anodes during lithium insertion and extraction at the same time. The synthesis process is very simple, providing a low-cost production approach toward high-performance energy storage materials.